THE ATTEMPTS TO IMPROVE BEGINNING READING SKILLS USING AUDIO-VISUAL FLASHCARD MEDIA AT PRIMARY SCHOOL - Nurul Diana Rosida; Rudi Ritonga (Jurnal Ilmiah Pendidikan Citra Bakti, 2023)
In the beginning reading skilss primary school specifically of first grade student still has a role in supporting the growth and development of students’ potential, including improving their reading skills, to achieve those objectives). The purpose of this research was to (1) describe beginning reading skills and (2) determine the effectiveness of audio-visual flashcard learning media in improving beginning reading skills. This study’s approach employed quantitative research with classroom action research. The data were analyzed quantitatively using the Kemmis and Taggart models, which were implemented in two cycles consisting of (1) planning, (2) implementing actions, (3) observation, and (4) reflection. The data was collected using observation, testing, and documentation techniques. The study’s findings indicated that using audio-visual flashcards could improve the beginning reading skills of first-grade students. This represents 59% of the 32 students. The study's findings indicated that using audio-visual flashcards could improve the reading skills of first-grade students. it was demonstrated that 84.4% or 27 students completed their courses, compared to the previous 19 students, or 59% of 32 students.